Problem-Based Learning (PBL) in Arabic Opinion Writing Learning - Rufaiqoh, Elok; Hasanah, Mamluatul; Syuhadak, Syuhadak; Asy’ari, Hasyim; ElJack Ibrahim, Nahla Ibrahim (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
Learning Arabic writing skills still faces many problems. Because this skill is the most difficult Arabic language skill compared to the other three Arabic language skills, in learning activities, an effective and efficient learning approach is needed to make students proficient in Arabic writing skills. This approach is the PBL Approach. An approach that emphasizes a problem as a learning trigger and students are asked to find solutions. So this research aims to reveal the application of PBL in learning Arabic writing skills at IAI Al-Qodiri Jember. The Arabic writing skill in question is writing opinions in Arabic and applying problem-based learning in learning Arabic opinion writing skills in the fifth-semester Arabic language education program. The approach used in this research is qualitative, with a case study type. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman analysis model which includes data presentation, reduction, and verification. The data validity technique used in this research is source triangulation, by comparing data obtained from field research and primary sources (library). The results of the research show that the application of PBL in learning Arabic opinion writing skills runs effectively and efficiently in both the learning and evaluation processes. Apart from that, the application of PBL can improve students' critical thinking skills in the form of the ability to analyze, evaluate, and create. This article can be used as a reference for educators in implementing PBL in learning Arabic writing skills at the tertiary level. Copyright: © 20xx by the author(s). This open-access article is distributed under the terms and conditions of the Creative Commons Attribution-ShareAlike (CC BY-SA) license (https://creativecommons.org/licenses/by-sa/4.0/).